Preparing Dutch Homes for Energy Transition - Prateek Wahi (A+BE: Architecture and the Built Environment)
Recent geopolitical events have driven a sharp rise in gas prices, making it increasingly difficult for households to heat their homes affordably and comfortably. Additionally, the environmental consequences of fossil fuel-based heating underscore the urgency of transitioning to more sustainable alternatives. In response, the Dutch government has set an ambitious target to eliminate natural gas heating in 1.5 million homes by 2030, emphasising the need for viable solutions. District heating (DH) systems, particularly those providing lower-temperature heating (LTH), offer a promising alternative—delivering sustainable and cost-effective heating, especially in densely populated areas. However, with their high heating demands, many existing homes require significant renovations before efficiently transitioning to LTH-based systems. The selection of appropriate renovation strategies is complex, often leading to uncertainty and delays.